UD.Sumber Rejeki Re-Branding Strategy To Increase Sales Turnover - Sumantoro, Harry; Imam, Muhammad; Sabri (International journal of technology and education research, 2023)
Business Model Canvas aims to help companies to recognize what is the company's value proposition, as well as how to build and run key activities and key resources in creating value propositions and getting revenue streams, understanding how the products and services offered by the company can be well communicated to consumers. Data from report documents in the form of hard copies and soft copies in UD. Sumber Rejeki is also as a company under study. The primary type of data is data that comes directly from data sources that are collected specifically and are related to problems that are examined by means of observation, interviews. Meanwhile, secondary data types are obtained through literature reviews, reviews of previous relevant research, documents and routine company reports. The result can be known the position of the company based on a review of SWOT and 5 Forces Porter, which shows that the company is UD. Sumber Rejeki still has a good enough opportunity to seize the market or consumers, where the strategy that can be used is to take advantage of the remaining processed soybeans with a selling value and change the branding of the product packaging and expand marketing. That way a new business model canvas remodeling can be made that is in line with the SWOT position and a new strategy that supports the implementation of the new business model canvas created.